Penguatan Karakter Siswa melalui Inovasi Pembelajaran di Sekolah Negeri - Agus Susilo; Siti Agusma; Marianita Marianita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Keguruan dan Ilmu Pendidikan PGRI Sampang, Indonesia, 2026)
This study aims to describe the strengthening of student character through learning innovations implemented in public schools. Character strengthening has become an important focus in education because technological developments and social changes require students to have not only academic abilities but also good character. This study used a qualitative approach with descriptive methods. The research location was conducted in a public school with research subjects consisting of principals, teachers, and students. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis used the stages of data reduction, data presentation, and conclusion drawing, while data validity was tested through triangulation of sources and techniques. The results showed that the learning innovations implemented by teachers were able to support the strengthening of student character through project-based learning, the use of digital media, collaborative discussions, and the habituation of character values ​​in learning activities. The character values ​​developed included discipline, responsibility, cooperation, creativity, and social awareness. In addition, school support and teacher involvement were important factors in the successful implementation of character strengthening. However, there were several obstacles such as limited facilities and differences in student character that influenced the process of implementing innovative learning. This study concludes that learning innovation has a strategic role in shaping the character of students in public schools, so it is necessary to develop creative and sustainable learning models to support character education in schools.